ENHANCED OFFICE ERGONOMICS: RASPBERRY PI-POWERED INTELLIGENT CHAIR - Neher Banu, Shaik; Gousiya, Begum; Shiva Kumar, Godi Sunny; Ganesh, B. (International Journal of Psychosocial Rehabilitation, 2019)
Longer hours are spent sitting in offices pertaining to software, working professors in schools, universities, etc. This has led to a growing number of health problems for them, including obesity, joint discomfort, back pain, and other ailments. The "Intelligent Office Chair" project was created as a solution to this. If a person sits on this chair for an extended period of time, it provides instructions. Additionally, you may use the app to change the height of this chair. A prototype module is created utilising a Raspberry Pi to demonstrate the idea in practice. We can change the height and set a siren to alert the user when they are sitting for longer than usual so they can take a short break by using the IP address. If the person is not seated correctly, an ultrasonic sensor is also utilised to provide instructions. The chair uses sensors to measure several factors, such as an infrared sensor to identify obstacles and an ultrasonic sensor to evaluate a person's posture distance. The Raspberry Pi, the most demanding technology, was used in the design of this project. According to preliminary findings, the Chair and the case study smartphone application can precisely identify the parameters and provide information or indications via the output devices, such as vibrators. IP addresses are important to this project since they allowed us to construct it. We are able to feel vibrations thanks to relays